The metamorphism and exhumation of the Himalayan metamorphic core, eastern Garhwal region, India - Spencer, Christopher; Harris, R.; Dorais, M.J. (American Geophysical Union, 2012)
[1] Geothermobarometric together with micro- and macro-structural data indicate ductile flow in the metamorphic core of the Himalaya in the Garhwal region of India. Peak metamorphic pressure and temperature increase dramatically across the Main Central Thrust (MCT) from ~5 kbar and ~550°C in the Lesser Himalayan Crystalline Sequence (LHCS) to ~14 kbar and ~850°C at ~3 km above the MCT in the Greater Himalayan Sequence (GHS). Pressures within the GHS then decrease upsection to ~8 kbar while temperatures remain nearly constant at ~850°C up to the structurally overlying South Tibetan Detachment (STD). The GHS exhibits sheath fold geometries are indicative of high degrees of ductile flow. Overprinting ductile structures are two populations of extensional conjugate fractures and normal faults oriented both parallel and perpendicular to the orogen. These fractures crosscut major tectonic boundaries in the region such as the MCT and STD, and are found throughout the LHCS, GHS, and Tethyan Sedimentary Sequence (TSS). The thermobarometric and metamorphic observations are consistent with a form of channel flow. However, channel flow does not account for exhumational structures that formed above the brittle-ductile transition. To explain all of the features seen in the metamorphic core of the Garhwal region of the Himalaya, both the theories of channel flow and critical taper must be taken into account. Channel flow can explain the exhumation of the GHS from the middle crust to the brittle-ductile transition. The most recent extensional deformation is consistent with a supercritical wedge.